Forest Symbolism in the Relationship Between Nature and Culture: A Study in the Oral Traditions of Ethnic Groups in the Central Highlands of Vietnam - Viet Hung Nguyen; Thi Dieu Khanh Nguyen (Journal of Language and Literature, 2026)
In the perception of most modern people, the forest is a natural entity, either coexisting with culture or standing in opposition to it – a concept that is understood to involve human factors influencing nature. From this, notions about forests and nature arise, accompanied by rules governing human interactions with nature, which are perceived as either egalitarian or hierarchical. When examining the oral traditions of the ethnic groups in the Central Highlands of Vietnam, we find that these communities consider themselves “the forest eaters” (G. Condominas, 2003), not only due to their economic activities, settlement, and the reckoning of time within the human life cycle, but also because all their beliefs, rituals, customs, and spiritual practices are deeply intertwined with the forest. The theoretical distinction that villages are associated with rituals while forests are not may not hold true for these indigenous communities. By applying discourse analysis theory (Foucault) and ecocriticism, this study examines myths, epics (khan), folktales, proverbs, and customary law texts of ethnic groups such as the Ede, Jarai, Mnong, and Raglai in the Central Highlands of Vietnam to redefine the concepts of forest, village, humanity, and the social space of the residents inhabiting these regions. The findings reveal that the forest functions simultaneously as a natural space parallel to social space, a sacred domain bound to spirit-world beliefs, and an essential source of livelihood and aesthetic inspiration. The study concludes that Central Highlands communities maintain a non-dualistic worldview in which nature and culture are inseparable, offering an alternative ontological perspective to the Western nature – culture dichotomy and contributing new insights to ecocritical and anthropological scholarship on indigenous ecological knowledge.